2020
DOI: 10.3390/ijerph17062018
|View full text |Cite
|
Sign up to set email alerts
|

Association between TUG and Anthropometric Values, Vibration Perception Threshold, FHSQ and 15-D in Type 2 Diabetes Mellitus Patients

Abstract: Background: Diabetes Mellitus (DM) is a chronic disease and it is characterized by reduced insulin sensitivity and/or impaired insulin production. It affects approximately 415 million people worldwide and involves a variety of complications. DM has a number of complications, including diabetic neuropathy. All of these complications can have effects on body composition, vibration perception threshold (VPT), foot health and health-related quality of life (HRQoL). Objective: The aim of this study is to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In Bergin’s study [ 47 ], vibration perception was increased in the patients with peripheral neuropathies, and there was a significant correlation between vibration sense and body sway. The results of our study are consistent with the results of previous studies for diabetic patients, which suggested that DPN assessed with various kinds of measurements was associated with postural steadiness and functional balance [ 14 , 29 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Bergin’s study [ 47 ], vibration perception was increased in the patients with peripheral neuropathies, and there was a significant correlation between vibration sense and body sway. The results of our study are consistent with the results of previous studies for diabetic patients, which suggested that DPN assessed with various kinds of measurements was associated with postural steadiness and functional balance [ 14 , 29 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with the association between TUG and height that was reported in the current study, but contradict the relation between TUG and weight and BMI that was reported in this manuscript. Domínguez-Muñoz et al [ 53 ] found a small inverse correlation (r = −0.23) between TUG and height, and a small direct correlation (r = 0.25) for TUG and BMI. These authors found a non-significant association between TUG and weight, which is the only disagreement with the present study, obviating the relation between TUG and WHR that these authors did not study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the exclusion criteria were as follows: (a) people diagnosed with type 1 DM, (b) people for whom high-intensity exercises are contraindicated or people suffering from any condition (like retinopathy, musculoskeletal injuries, significant equilibrium issues, or an increased risk of thrombus) that contraindicates such exercises, (c) people under psychotropic or neurotoxic treatment or exposed to neurotoxins (e.g., from industrial accidents or contact with toxic residues), (d) people receiving radiation therapy, (e) people under high risk of nondiabetic neuropathy (such as HIV, alcoholism, or uremia), (f) people highly exposed to whole-body vibration at work, and (g) people having participated in previous whole-body vibration studies. The data for the sample characterization can be found in Table 1 of the article by Domínguez-Muñoz et al [28]. Prior to the start of participant recruitment, a sample size estimation was conducted.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Although previous studies have reported the relationship between anthropometrics, FHSQ, 15-D questionnaire, and VPT with other tests such as the timed up and go test (TUG) in T2DM patients [ 28 ], no studies have analyzed the relationship between these assessments and the 30-s chair stand-up test. Thus, this study aimed to explore the possible relationships between the 30-s chair stand-up test and anthropometrics, 15-D questionnaire, FHSQ, and VPT in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%